Investigations into the Combined Effect of Mahua Biodiesel Blends and Biogas in a Dual Fuel Engine - Anmol Singh Kshatriya; Prabhatkumar Tiwari; Sreekanth M; T. M. Yunus Khan; Shaik Dawood Abdul Khadar; Mohamed Mansour; Feroskhan M (Energies, 2022)
Rapid depletion of conventional fuel sources has led to the use of alternative fuels and implementation of variant engine technologies to reduce deleterious emissions being released and deliver thermal energy for numerous applications. This research aims to study the usage of mahua methyl ester in a single-cylinder 4-stroke CI engine, optimized to operate in the dual fuel mode. Performance, combustion and emission characteristics are recorded and compared with diesel with the sole aim of finding the blend that provides adequate performance and diminishing emissions. To this effect, the percentage of mahua biodiesel blend, load, biogas flow rate and methane fraction are varied. The experimentation is conducted using three mahua biodiesel blend variants namely B10, B20 and B30. Gaseous fuel comprising biogas (CH4 and CO2 in ratio of 3:2) and methane (CH4) are incorporated in the dual fuel condition at 8 litre per minute (lpm) and 12 lpm. B20 blend demonstrated better performance and emission characteristics. The addition of biodiesel (B20) showed more than 5% improvement in brake thermal efficiency. Additionally, comparing with normal diesel mode, B20 showed lower CO (0.061%) and NOx (615 ppm) emissions. In the dual fuel condition, methane and biogas are effective in reducing the NOx emissions, but with a negative repercussion of extortionately elevated HC and CO emissions. The best combination is deduced to be B20 mahua biodiesel at 8 lpm of biogas flow rate in the dual fuel mode due to better performance and emission characteristics.